Analisis Yuridis atas Putusan Praperadilan Kasus Korupsi Eks Wamenkumham oleh Hakim Pengadilan - Amos Aldy Bessie; Reny R. Masu; Orpa G. Manuain (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Corruption is one of the serious problems currently being faced by many countries in the world, including our country Indonesia. Not only does it harm the country's economy, corruption has also been proven to hinder the development of a country and create social injustice. This study aims to determine the basis for the judge's considerations in granting a pretrial motion by the former deputy minister of law and human rights and than the judge's decision related to the determination of the suspect in the pretrial motion. The method used in this study is normative legal research with a Legislation approach, Conceptual Approach, and Case Approach. The data collection technique used is library research, the data is collected and then analyzed using descriptive qualitative analysis. The results of the study show that the basis for the judge's considerations in the pretrial motion decision on the Eddy Hiariej case shows the judge's tendency to focus more on formal aspects than material aspects. The judge's decision in granting a pretrial motion, especially in corruption cases such as the Eddy Hiariej case, the judge should not limit his considerations only to the due process of law aspect which emphasizes procedural accuracy. However, on the other hand, judges are also required to pay attention to the dimensions of the crime control model, which emphasizes the effectiveness of eradicating crime, as well as the principle of substantive justice, which demands justice based on material truth.